Atomic ash for high-speed rail and preparation method thereof

By using two-component multi-function light putty in high-speed rail body coatings and adding tung oil, dicyandiamide and barium ferrite to polyester resin, the coating is heat-resistant and corrosion-resistant under high electromagnetic radiation environments. The problem of insufficient performance achieves efficient and durable coating protection effect.

CN118421128BActive Publication Date: 2025-02-11GUANGZHOU ZHONGHAN CHUANGNENG NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410656465.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-24
Publication Date
2025-02-11
Estimated Expiration
2044-05-24

AI Technical Summary

Technical Problem

The prior art is difficult to provide atomic ash coatings with high heat resistance, corrosion resistance, adhesion and flexibility to high-speed rail vehicles in a high electromagnetic radiation environment.

Method used

Using two-component multifunctional light putty, component A includes modified polyester resin, styrene, dispersant, stabilizer, wetting agent and filler, component B is cyclohexanone peroxide, through the polyester resin Add tung oil, dicyandiamide, barium ferrite, cobalt oxide and other components to improve the adhesion, heat resistance and electromagnetic radiation resistance of the paint.

Benefits of technology

It achieves long durability under high electromagnetic radiation conditions, improves the heat resistance, corrosion resistance, adhesion and flexibility of the paint, extends the construction area and construction efficiency, and improves the protection effect of the surface of the high-speed rail car body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004857972590000081
    Figure BDA0004857972590000081
Patent Text Reader

Abstract

The invention belongs to the technical field of coatings and relates to an atomic putty for high-speed rail and a preparation method thereof. The atomic putty comprises the following components: a component A and a component B, wherein the component A comprises a modified polyester resin, styrene, a dispersant, a stabilizer, a wetting agent, and a rust inhibitor, and the component B comprises cyclohexanone peroxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of atomic ash, and relates to atomic ash for high-speed rail and a preparation method thereof. Background Art

[0002] Putty is a special coating, which is characterized by being able to produce special optical effects under the irradiation of light, making the surface present a metallic texture or pearlescent texture. Putty coating is commonly used for spray painting of vehicles such as cars, motorcycles, bicycles, and surface decoration of objects such as furniture and buildings. It can make the surface of an object present a noble and luxurious metallic texture, while still retaining a delicate and smooth touch. In the automotive industry, putty coating is commonly used for exterior spraying of high-end luxury models to increase the visual effect and added value of the vehicle. However, in the prior art, although there are putties applied to various means of transportation, for putties used in high-speed rail, it requires special corrosion resistance, heat resistance, adhesion and flexibility. Due to the high-speed operation environment of the high-speed rail, as well as electromagnetic radiation, it has special requirements for the heat resistance, corrosion resistance, adhesion and flexibility of the body surface coating in a high electromagnetic radiation environment.

[0003] Based on the above analysis, it is very necessary to provide a method for finding a suitable formula while ensuring the curing efficiency of the putty, so as to keep the putty having high heat resistance, corrosion resistance, adhesion and flexibility. Summary of the invention

[0004] The present application provides an atomic putty for high-speed rail and a preparation method thereof. The atomic putty is a two-component multifunctional lightweight putty, which has the advantages of fast curing and strong adhesion, is suitable for high-speed rail metal substrates, has a long durability under high electromagnetic radiation conditions, is heat-resistant, and has high adhesion and flexibility. Compared with heavy putty of the same quality, it has a larger construction area, higher construction efficiency, longer durability in the operating environment of high-speed rail, and achieves a longer replacement interval and re-coating time.

[0005] The technical solution of the present invention is to provide an atomic ash for high-speed rail, characterized in that it is composed of component A and component B, wherein component A comprises the following components in weight percentage: 45-60 parts of modified polyester resin, 5-20 parts of styrene, 0.5-5 parts of dispersant, 0.5-1 parts of stabilizer, 0.1-1 parts of wetting agent, and the balance is filler, component B comprises cyclohexanone peroxide, and the weight ratio of component A to component B is 100:2;

[0006] Furthermore, the stabilizer model is: BASF Tinuvin 292;

[0007] Furthermore, the filler is composed of pearl powder and fluorite balls in a mass ratio of 1:1;

[0008] Further, the dispersant model is: BASF EFKA PX4310;

[0009] Further, the wetting agent model is: TEGO254;

[0010] Furthermore, the modified polyester resin is prepared by the following process:

[0011] Step 1: Load a multi-component acid, a multi-component alcohol, trimethylolpropane diallyl ether, and monobutyl tin oxide into a filling column, and add p-hydroxyanisole; the mass of trimethylolpropane diallyl ether is 6% to 8% of the mass of the multi-component acid, the mass of monobutyl tin oxide is 8% to 9% of the mass of the multi-component acid, and the mass of p-hydroxyanisole is 0.1% to 0.2% of the total mass of the multi-component acid and the multi-component alcohol; the multi-component acid is specifically adipic acid, isophthalic acid, and succinic acid in a weight ratio of 1:2:1; the multi-component alcohol is specifically 2-methyl-1,3-propanediol, 1,4-cyclohexanedimethanol, and 1,2-propylene glycol in a weight ratio of 7:3:2, and the mass ratio of the multi-component acid to the multi-component alcohol is 1:1;

[0012] Step 2: Esterification and dehydration at 130-138°C for 2h to 3h;

[0013] Step 3: Raise the temperature to 190-195°C, keep the temperature constant for at least 3 hours, measure the acid value every 10 minutes, and when the acid value is 91-95 mg KOH / g, add tung oil and cool to 145-150°C, the mass of tung oil is 5% of the mass of the multi-component acid;

[0014] Step 4: the temperature is gradually raised to 180-188°C, N-methylpyrrolidone is added, the mass of N-methylpyrrolidone is 1% of the mass of the multi-component acid, the temperature is kept for 1 hour, the acid value is measured every 10 minutes, and when the acid value is 65 mg KOH / g, the reaction container is evacuated, and the vacuum dehydration time is 2 hours;

[0015] Step 5: adding styrene to dilute, reacting for 1 hour, gradually cooling to 85-90° C. to obtain a polyester resin raw material, wherein the amount of styrene added is 40% of the total mass of the multi-component acid and the multi-component alcohol in step 1;

[0016] Step 6: Divide the prepared polyester resin raw material into two equal parts, denoted as component A1 and component A2.

[0017] Add dicyandiamide to component A1, the added mass of dicyandiamide is 30% of component A1, then add phenol, the added mass of phenol is 70% of the mass of component A1, slowly evaporate the phenol at 74-76° C. for 24 hours until it is evaporated to dryness, then vacuumize at 45-55° C., add styrene to the obtained powdery substance for dilution, the mass of styrene is 5 times that of the powdery substance, let it stand for 1 hour after dilution, and cool to 40° C. to obtain a polyester resin modified with an amine compound;

[0018] Step 7: iron nitrate Fe(NO 3 ) 3 9H 2 O.Ba 3 N 2 Place in deionized water to make the molar ratio of Fe:Ba be 10:1, then add citric acid to the deionized water, the mass of citric acid added is 5% of the mass of deionized water, stand for 3 hours and set aside, recorded as solution C1; separately take cobalt nitrate hexahydrate and add it to the solvent, the solvent is ethylene glycol, the mass ratio of cobalt nitrate hexahydrate to the solvent is 1:3, start the synthesis process, then stir vigorously for 2 hours until the solid is completely dissolved at room temperature, stand for 1 hour and set aside, obtain solution C2, respectively place solution C1 and solution C2 on a heating device and evaporate to dryness at a constant temperature, control the temperature to 75°C, obtain water-free gel D1 and gel D2, add gel D1 and gel D2 to component A2, control gel D1 and gel D2 to be 1% and 0.5% of the mass of component A2 respectively, stir evenly, and obtain a polyester resin containing barium ferrite and cobalt oxide;

[0019] Step 8: uniformly mixing the polyester resin modified with the amine compound obtained in step 6 and the polyester resin containing barium ferrite and cobalt oxide obtained in step 7 to obtain a modified polyester resin;

[0020] Furthermore, the present application also provides a method for preparing the above-mentioned high-iron putty, comprising the following steps: mixing and dispersing the modified polyester resin, styrene, a dispersant, a stabilizer, and a wetting agent until the mixture is uniform; then adding a filler and continuing to disperse for 2 hours to obtain component A;

[0021] Furthermore, the method also includes the following steps: removing oil and moisture from the surface of the coated object before use to keep the surface of the coated object clean and dry; before using the putty, shaking the vacuum sealed can containing the putty, then pouring out component A and component B, and mixing them in a weight ratio of 100:2, and completing the scraping within 8 minutes.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The present application improves the adhesion and flexibility of the putty by adding tung oil during the preparation of the polyester resin.

[0024] (2) The present application adds amine compounds, especially dicyandiamide, during the polyester resin modification process, which improves the heat resistance of the putty by introducing nitrogen-containing elements.

[0025] (3) High-speed trains generate electromagnetic radiation during operation, mainly from the train's motors, transformers and electrical equipment. These devices generate magnetic fields through electric currents, thereby generating electromagnetic radiation. This will have a certain impact on passengers inside the high-speed train. On the other hand, electromagnetic radiation acts on the surface of the metal carriages of the high-speed train, which can easily cause the surface of the high-speed train to heat up, causing the paint to age faster. This application adds barium ferrite and cobalt oxide to the polyester resin component. The addition of these two substances improves the electromagnetic radiation resistance of the polyester resin, thereby improving its durability. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] A putty for high-speed rail, characterized in that it consists of component A and component B, wherein component A is made of the following components in weight percentage: 53 parts of modified polyester resin, 12 parts of styrene, 2.5 parts of dispersant, 0.7 parts of stabilizer, 0.5 parts of wetting agent, and the balance is filler; component B is cyclohexanone peroxide; the weight ratio of component A to component B is 100:2;

[0029] Among them, the dispersant model is: BASF EFKA PX4310;

[0030] The stabilizer model is: BASF Tinuvin 292;

[0031] Wetting agent model: TEGO254;

[0032] The filler is made of pearl powder and fluorite balls in a mass ratio of 1:1;

[0033] The preparation process of the modified polyester resin comprises the following steps: step 1: loading a multi-component acid, a multi-component alcohol, trimethylolpropane diallyl ether, and monobutyl tin oxide into a filling column, and adding p-hydroxyanisole; the mass of trimethylolpropane diallyl ether is 7% of the mass of the multi-component acid, the mass of monobutyl tin oxide is 9% of the mass of the multi-component acid, and the mass of p-hydroxyanisole is 0.1% of the total mass of the multi-component acid and the multi-component alcohol; the multi-component acid is specifically adipic acid, isophthalic acid, and succinic acid in a weight ratio of 1:2:1; the multi-component alcohol is specifically 2-methyl 1,3-propanediol, 1,4-cyclohexanedimethanol, and 1,2-propylene glycol in a weight ratio of 7:3:2, and the mass ratio of the multi-component acid to the multi-component alcohol is 1:1;

[0034] Step 2: esterification and dehydration at 137°C for 2.5h;

[0035] Step 3: Raise the temperature to 192°C, and react at a constant temperature for at least 3 hours. Measure the acid value every 10 minutes. When the acid value is 93 mgKOH / g, add tung oil and cool down to 150°C. The mass of tung oil is 5% of the mass of the multi-component acid.

[0036] Step 4: the temperature is gradually raised to 185°C, N-methylpyrrolidone is added, the mass of N-methylpyrrolidone is 1% of the mass of the multi-component acid, the temperature is kept for 1 hour, the acid value is measured every 10 minutes, and when the acid value is 65 mg KOH / g, the reaction container is evacuated, and the vacuum dehydration time is 2 hours;

[0037] Step 5: adding styrene to dilute, reacting for 1 hour, and gradually cooling to 88° C. to obtain a polyester resin raw material, wherein the amount of styrene added is 40% of the total mass of the multi-component acid and the multi-component alcohol in step 1;

[0038] Step 6: Divide the prepared polyester resin raw material into two equal parts, denoted as component A1 and component A2.

[0039] Add dicyandiamide to component A1, the added mass of dicyandiamide is 30% of component A1, then add phenol, the added mass of phenol is 70% of the mass of component A1, slowly evaporate the phenol at 75°C for 24 hours until it is evaporated to dryness, then vacuumize at 50°C, add styrene to dilute the obtained powdery substance, the mass of styrene is 5 times that of the powdery substance, let it stand for 1 hour after dilution, and cool to 40°C to obtain a polyester resin modified with an amine compound;

[0040] Step 7: iron nitrate Fe(NO 3 ) 3 9H 2 O.Ba 3 N 2Place in deionized water to make the molar ratio of Fe:Ba be 10:1, then add citric acid to the deionized water, the mass of citric acid added is 5% of the mass of deionized water, stand for 3 hours and set aside, recorded as solution C1; separately take cobalt nitrate hexahydrate and add it to ethylene glycol solvent, the mass ratio of cobalt nitrate hexahydrate to ethylene glycol solvent is 1:3, start the synthesis process, then stir vigorously for 2 hours until the solid is completely dissolved at room temperature, stand for 1 hour and set aside, obtain solution C2, respectively place solution C1 and solution C2 on a heating device and evaporate to dryness at a constant temperature, control the temperature to 75°C, obtain water-free gel D1 and gel D2, add gel D1 and gel D2 to component A2, control gel D1 and gel D2 to be 1% and 0.5% of the mass of component A2 respectively, stir evenly, and obtain a polyester resin containing barium ferrite and cobalt oxide nanopowder;

[0041] Step eight: uniformly mix the polyester resin modified with the amine compound obtained in step six and the polyester resin containing barium ferrite and cobalt oxide nanopowder obtained in step seven to obtain a modified polyester resin.

[0042] Specifically, the dosage of each raw material is as follows:

[0043] Adipic acid: 30 g;

[0044] Isophthalic acid: 60g;

[0045] Succinic acid: 30g;

[0046] 2-Methyl 1,3-propanediol: 70g;

[0047] 1,4-cyclohexanedimethanol: 30 g;

[0048] 1,2-Propanediol: 20g;

[0049] Tung oil: 6g;

[0050] Trimethylolpropane diallyl ether: 8.4 g;

[0051] Monobutyltin oxide: 10.8g;

[0052] p-Hydroxyanisole: 0.24 g;

[0053] N-methylpyrrolidone: 1.2 g;

[0054] In step 5, the amount of styrene added: 96 g;

[0055] In step 7, Fe(NO 3 ) 3 9H 2 The amount of O used was 23 g, the molar ratio of Fe:Ba was 10:1, and deionized water was 500 ml.

[0056] Example 2

[0057] A putty for high-speed rail, which is different from Example 1 in that: in the preparation process of the modified polyester resin, an equal mass of arachidonic acid is used instead of tung oil.

[0058] Example 3

[0059] A putty for high-speed rail, which is different from Example 1 in that: in the preparation process of the modified polyester resin, an equal mass of linoleic acid is used instead of tung oil.

[0060] Example 4

[0061] A putty for high-speed rail, which is different from Example 1 in that tung oil is not used in the preparation process of the modified polyester resin.

[0062] Example 5

[0063] A putty for high-speed rail, which is different from Example 1 in that: during the preparation of the modified polyester resin, the polyester resin of component A1 is not modified with dicyandiamide, and the polyester resin of component A1 is directly mixed with the polyester resin containing barium ferrite and cobalt oxide nanopowder obtained in step 7 to obtain the modified polyester resin.

[0064] Example 6

[0065] An atomic putty for high-speed rail, which is different from Example 1 in that: during the preparation of the modified polyester resin, the component A2 does not add the gel D1, but only adds the gel D2 whose mass is 1.5% of the mass of the component A2.

[0066] Example 7

[0067] An atomic putty for high-speed rail, which is different from Example 1 in that: during the preparation of the modified polyester resin, the component A2 does not add the gel D2, but only adds the gel D1 with a mass that is 1.5% of the mass of the component A2.

[0068] Example 8

[0069] An atomic putty for high-speed rail, which is different from Example 1 in that: during the preparation of the modified polyester resin, the component A2 does not add gel D1 and gel D2, but only adds silicon dioxide in an amount of 1.5% of the mass of the component A2.

[0070] The performance of the atomic ash used for high-speed rail in the above Examples 1-8 was tested, and the test method is shown in the following table:

[0071] Table 1

[0072]

[0073] Note: The special experimental condition means that the mixed putty of component A and component B is coated on the surface of the hollow glass container, and after solidification, a field strength of 200 microtesla is applied to the outside of the hollow glass container, and the field strength inside the glass container is measured.

[0074] Through the above experiments, it can be found that by comparing Examples 1-4, tung oil improves the adhesion and flexibility of the putty. By comparing Example 5 with Example 1, and by comparing Example 5 with other examples, it can be seen that dicyandiamide improves the heat resistance of the putty by introducing nitrogen-containing elements. By comparing Examples 6-8 with Example 1, it can be seen that barium ferrite and cobalt oxide can significantly improve the electromagnetic radiation resistance of polyester resin, thereby improving its durability during high-speed rail operation, and also hindering the impact of electromagnetic radiation on passengers to a certain extent.

[0075] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A kind of atomic ash for high-speed rail, characterized in that: It is composed of component A and component B, wherein component A includes the following components in weight percentage: 45-60 parts of modified polyester resin, 5-20 parts of styrene, 0.5-5 parts of dispersant, 0.5-1 parts of stabilizer, 0.1-1 parts of wetting agent, and the balance is filler; component B includes cyclohexanone peroxide; wherein the weight ratio of component A to component B is 100:2; The filler is composed of pearl powder and fluorite balls in a mass ratio of 1:1; the modified polyester resin is prepared by the following process: Step 1: Load a multi-component acid, a multi-component alcohol, trimethylolpropane diallyl ether, and monobutyl tin oxide into a filling column, and add p-hydroxyanisole; the mass of trimethylolpropane diallyl ether is 7% of the mass of the multi-component acid, the mass of monobutyl tin oxide is 9% of the mass of the multi-component acid, and the mass of p-hydroxyanisole is 0.1% of the total mass of the multi-component acid and the multi-component alcohol; the multi-component acid is specifically adipic acid, isophthalic acid, and succinic acid in a weight ratio of 1:2:1; the multi-component alcohol is specifically 2-methyl-1,3-propanediol, 1,4-cyclohexanedimethanol, and 1,2-propylene glycol in a weight ratio of 7:3:2, and the mass ratio of the multi-component acid to the multi-component alcohol is 1:1; Step 2: esterification and dehydration at 130-138°C for 2.5h; Step 3: Raise the temperature to 190-195°C, keep the temperature constant for at least 3 hours, measure the acid value every 10 minutes, and when the acid value is 91-95 mgKOH / g, add tung oil and cool down to 150°C. The mass of tung oil is 5% of the mass of the multi-component acid. Step 4: gradually increase the temperature to 180-188°C, add N-methylpyrrolidone, the mass of N-methylpyrrolidone is 1% of the mass of the multi-component acid, keep warm for 1 hour, measure the acid value every 10 minutes, when the acid value is 65 mg KOH / g, evacuate the reaction container, and the vacuum dehydration time is 2 hours; Step 5: adding styrene to dilute, reacting for 1 hour, gradually cooling to 85-90°C to obtain a polyester resin raw material, wherein the amount of styrene added is 40% of the total mass of the multi-component acid and the multi-component alcohol in step 1; Step 6: Divide the prepared polyester resin raw material into two equal parts, denoted as component A1 and component A2. Add dicyandiamide to component A1, the added mass of dicyandiamide is 30% of component A1, then add phenol, the added mass of phenol is 70% of the mass of component A1, slowly evaporate the phenol at 75° C. for 24 hours until it is evaporated to dryness, then vacuumize at 50° C., add styrene to the obtained powdery substance for dilution, the mass of styrene is 5 times that of the powdery substance, let it stand for 1 hour after dilution, and cool to 40° C. to obtain a polyester resin modified with an amine compound; Step seven, put iron nitrate Fe(NO3)3·9H2O and Ba3N2 into deionized water to make the molar ratio of Fe:Ba be 10:1, then add citric acid into deionized water, the mass of citric acid added is 5% of the mass of deionized water, stand for 3 hours and set aside, recorded as solution C1; separately take cobalt nitrate hexahydrate and add it to the solvent, the mass ratio of cobalt nitrate hexahydrate to the solvent is 1:3, start the synthesis process, then stir vigorously for 2 hours until the solid is completely dissolved at room temperature, stand for 1 hour and set aside, obtain solution C2, respectively place solution C1 and solution C2 on a heating device and evaporate to dryness at a constant temperature, control the temperature to 75°C, obtain water-free gel D1 and gel D2, add gel D1 and gel D2 into component A2, control the mass of gel D1 and gel D2 to be 1% and 0.5% of the mass of component A2 respectively, stir evenly, and obtain a polyester resin containing barium ferrite and cobalt oxide nanopowder; Step eight: uniformly mix the polyester resin modified with the amine compound obtained in step six and the polyester resin containing barium ferrite and cobalt oxide nanopowder obtained in step seven to obtain a modified polyester resin.

2. The atomic ash for high-speed rail as claimed in claim 1, wherein the stabilizer model is: BASF Tinuvin 292.

3. The atomic ash for high-speed rail as claimed in claim 1, wherein the dispersant model is: BASF EFKA PX4310.

4. The atomic ash for high-speed rail according to claim 1, characterized in that: The dissolving agent in step seven is ethylene glycol.

5. The method for preparing atomic ash for high-speed rail according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing and dispersing the modified polyester resin, styrene, a dispersant, a stabilizer and a wetting agent until the mixture is uniform; then adding a filler and continuing to disperse the mixture for 2 hours to obtain component A.

6. The method for preparing atomic ash for high-speed rail according to any one of claims 1 to 4, characterized in that: Before use, remove oil and moisture from the surface of the coated object, keep the surface of the coated object clean and dry. Before using the putty, shake the vacuum sealed can containing the putty, then pour out component A and component B, mix them in a weight ratio of 100:2, and apply them within 8 minutes.

Citation Information

Patent Citations

  • High-iron putty and preparation method thereof

    CN110616005A

  • High-temperature-resistant organic amine modified polyester resin and preparation method and application thereof

    CN111205446A